Cellular automaton simulation of ferrite-austenite transformation in low-carbon steels. Issue 1 (May 2015) - An, D; Pan, S; Yu, Q; Lin, C; Dai, T; Krakauer, B W; Zhu, M
Abstract: A two-dimensional (2-D) cellular automaton (CA) model is adopted to simulate ferrite (α)-austenite (γ) transformation in low-carbon steels. In the model, the preferential nucleation sites of austenite, the driving force of phase transformation coupled with thermodynamic parameters, solute partition at the α/γ interface, and carbon diffusion in both the α and γ phases are taken into consideration. The model is able to simulate the ferrite-to- austenite transformation during isothermal heating in the ferrite-austenite two-phase region, and the austenite-to-ferrite transformation during continuous cooling. The influences of cooling rate and α grain size on the final carbon concentration field are investigated. The results show that after isothermal heating at 815°C for 300 s, the carbon concentration in both the α and γ phases reach the respective equilibrium values. The simulated microstructures compare well with the SEM images. After cooling to room temperature, the carbon distribution is more uniform when cooled at 1.2°C/s than at 7°C/s. The carbon distributions for different α grain sizes cooled at 1.2°C/s are similar. The simulation results are used to understand the mechanisms of the experimental phenomena of an enameling steel.